Emerging vector borne diseases as public health threats and diseases of trade. The case of Rift Valley fever: a threat to livestock trade and food security in the Horn of Africa - Tibbo, Markos; Workalemahu, A.; Bonnet, P. (EVA, 2002)
Rift Valley Fever (RVF) is a viral zoonotic insect-borne disease of livestock and human beings caused by a member of the Phlebovirus genus of the family Bunyaviridae. Being first recognised in the Rift Valley of Kenya at the turn of 20th century, several epidemics have occurred in eastern, southern, and northern Africa becoming a continental problem. The epidemics that occurred in Egypt in 1977-78 and current human and animal cases in Yemen and Saudi Arabia (first case out of Africa) indicated the potential for spread to other inter-tropical regions of the world outside the African continent. An embargo on livestock export by Gulf countries has brought in food insecurity in the East African countries due to indirect socio-economic mechanisms and impact of ban on pastoralists household economy. Food insecurity in the Horn of Africa is a longstanding problem while the recent ban was imposed on eight countries before recovering from the recent drought of 2000. Between September and December 2000, a drop of livestock export by 92% was observed in Somalia. According to FSAU/FEWS (2001) excluding reduced governments revenue from livestock taxes, the estimated global loss of income at the Somali owner/producer level (including livestock originated from Region V of Ethiopia), lost producer income has reached 20-30 millions of USD, from October to December 2000. In Somalia, about 80% of foreign exchange earned from livestock exports are used to import basic food items and other commodities. The decrease in imported commodities and falling of local currency against the US dollar and an increase in the prices of imported commodities were the first symptoms observed in Somalia. This review emphasises on epidemiology, the risk of RVF on the future livestock economy and consequent food security in the Horn of Africa, and analyses the current situation in severely suffering regions and suggests and analyses international experience and short- and long-term solutions for the problem.